Animal domestication - Driscoll, Carlos A. (Henry Stewart Talks, 2014)
There are commonalities among domestic mammals that hint at common metabolic and genetic pathways, Domestication is genetic, heritable and selectable, Genes behind domestication are related to personality in humans.